Prolonged Sterile Dysuria as a First Presentation of Pyocolpos (Iranian Journal of Kidney Diseases, 2010)
Pyocolpos is a rare clinical finding in vaginal atresia, especially in childhood. We present a child with pyocolpos and a long history of severe sterile dysuria before she was admitted to hospital with fever, urinary tract infection, and abdominal mass.